A systematic review and meta‐analysis of respiratory dysfunction in Parkinson's disease. (7th March 2023) - McMahon, Laura; Blake, Catherine; Lennon, Olive
Abstract: Introduction: Respiratory dysfunction in Parkinson's disease (PD) is common and associated with increased hospital admission and mortality rates. Central and peripheral mechanisms have been proposed in PD. To date no systematic review identifies the extent and type of respiratory impairments in PD compared with healthy controls. Methods: PubMed, EMBASE, CINAHL, Web of Science, Pedro, MEDLINE, Cochrane Library and OpenGrey were searched from inception to December 2021 to identify case–control studies reporting respiratory measures in PD and matched controls. Results: Thirty‐nine studies met inclusion criteria, the majority with low risk of bias across Risk of Bias Assessment tool for Non‐randomized Studies (RoBANS) domains. Data permitted pooled analysis for 26 distinct respiratory measures. High‐to‐moderate certainty evidence of impairment in PD was identified for vital capacity (standardised mean difference [SMD] 0.75; 95% CI 0.45–1.05; p  < 0.00001; I 2  = 10%), total chest wall volume (SMD 0.38; 95% CI 0.09–0.68; p = 0.01; I 2  = 0%), maximum inspiratory pressure (SMD 0.91; 95% CI 0.64–1.19; p  < 0.00001; I 2  = 43%) and sniff nasal inspiratory pressure (SMD 0.58; 95% CI 0.30–0.87; p  < 0.00001; I 2  = 0%). Sensitivity analysis provided high‐moderate certainty evidence of impairment for forced vital capacity and forced expiratory volume in 1 s during medication ON phases and increased respiratory rate during OFF phases. Lower certainty evidence identified impairments in PD for maximum expiratory pressure, tidal volume, maximum voluntary ventilation and peak cough flow. Conclusions: Strong evidence supports a restrictive pattern with inspiratory muscle weakness in PD compared with healthy controls. Limited data for central impairment were identified with inconclusive findings.